Predicting success at vbac – a review of vbacs at the royal surrey county hospital. (18th April 2012) - Osborn, A; Morton, K
Abstract : Objectives: To review the notes of women with one previous CS who opted for VBAC in order to investigate whether successful VBAC outcome can be predicted from the labour history at CS and antenatal factors leading up to VBAC. Background: Over 2 years 704 women gave birth with one previous CS. A total of 364 women opted for VBAC with a success rate of 65%, of these 288 notes were audited. Methods: All patients coded as 1 previous caesarean section admitted to labour ward for time period January 2009– December 2010. A predesigned proforma was used for retrospective data collection. Information collected on indication and dilation at previous CS, antenatal health, gestation at VBAC and outcome. Results: 70% of women with fully dilated cervix in comparison to 40% with no cervical dilation before initial CS, had a successful VBAC (p=0.022). The successful cohort had a lower mean BMI (24.1 vs. 25.9 kg/m2, p=0.014) and significantly less antenatal illness (10% vs. 33%, p=0.004) than the unsuccessful cohort. Significantly more successful VBACs delivered at term (66% vs. 44% p=0.027), whereas 45% of unsuccessful VBACs delivered postdates despite equivalent use of induction. Conclusion: These results indicate that VBAC outcome correlates with: dilation of the cervix at CS, antenatal wellbeing and gestation at time of delivery. This enables practitioners to identify women most likely to achieve a successful VBAC and puts forward a case for allowing uncomplicated elective CS, labour to a certain point and offering membrane sweep before 41 weeks gestation at VBAC.